Oral Morphine Consumption Reduces Lens Development in Rat Embryos - Hossein Bahadoran; Fatemeh Rostamkhani; Hedayat Sahraei; Homeira Zardooz; Hassan Ghoshoni; Sara Sadeghi-Gharachdaghi; Elaheh Tekieh; Masoomeh Kazemi (Basic and Clinical Neuroscience, 2012)
Objective: Consumption of morphine, during pregnancy, in addition to inducing defects in the mother’s nervous system function, caused defects or delays in the formation and evolution of embryonic visual system. In the present study, changes in lens development was assessed in embryos exposed in utero to morphine. Material and Methods: Female Wistar rats (250-300 g) were mated with male rats and pregnancy was determined by sperm observation in vaginal smear. This day was considered as embryonic day zero (E0). The females were then divided randomly into the experimental and the control groups. The control group received tap water and the experimental group received morphine (0.05 mg/ml) in their water. On embryonic day 13 ( E13), blood samples were collected from the retro-orbital sinus of all animals for plasma corticosterone detection. On embryonic day 17(E17), the animals were killed by an overdose of chloroform and the embryos were taken out surgically. The embryos were fixed in 10% formalin for 30 days. At this time, the head of the embryos were removed for tissue processing and Hematoxylin- Eosin (H&E) staining. The samples were evaluated using light microscope and MOTIC software. Results: Our data indicated that plasma corticosterone level was dramatically increased and the lens was thinner in the experimental group. (Although the proliferation of lens cells increased in the experiment group but that lens had delay in removing the proliferated and elongation cells with abnormal density in the lateral part of the lens in compare with control group.) I have no idea what the authors are stating here. Moreover, the opening of the eyelids was delayed in the off springs of the mothers who received morphine. Conclusions: This study showed that morphine consumption during pregnancy leads to defects in fetal visual system development, particularly in the lens, and eyelids.